2010
DOI: 10.1007/s10620-010-1423-y
|View full text |Cite
|
Sign up to set email alerts
|

Initial Virological Response and Viral Mutation with Adefovir Dipivoxil Added to Ongoing Lamivudine Therapy in Lamivudine-Resistant Chronic Hepatitis B

Abstract: IVR is useful for predicting the antiviral efficacy of ADV and LAM combination therapy in LAM-resistant CHB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…In the present study, ETV resulted in less ETVresistant mutations in NUC-naive Japanese patients than in previous reports with other drugs such as 3TC [5,18]. In conclusion, attention should be paid to patients with poor adherence as well as emerging ETV-resistant mutations in HBV during ETV-treatment.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…In the present study, ETV resulted in less ETVresistant mutations in NUC-naive Japanese patients than in previous reports with other drugs such as 3TC [5,18]. In conclusion, attention should be paid to patients with poor adherence as well as emerging ETV-resistant mutations in HBV during ETV-treatment.…”
Section: Discussioncontrasting
confidence: 45%
“…In conclusion, attention should be paid to patients with poor adherence as well as emerging ETV-resistant mutations in HBV during ETV-treatment. [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ADV add-on LAM rescue therapy has shown acceptable antiviral efficacy in patients with LAM-resistant CHB [27,28], patients with a suboptimal response to this antiviral regimen have emerged [29,30]. However, this situation seems difficult to handle by changing or adding another antiviral agent, because the number of available potent NUCs with a high genetic barrier is significantly limited.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from interferon, with the use of NUCs such as entecavir and tenofovir, it is always possible for resistant mutants to emerge [97][98][99][100][101] . Suzuki et al [101] reported that 51-year-old Japanese women with chronic hepatitis B and cirrhosis have virological breakthrough during combination therapy with tenofovir and entecavir against entecavir-resistant virus.…”
Section: Stoppage Of Entecavir or Tenofovirmentioning
confidence: 99%